Response of the thermophile Thermus sp. RQ-1 to hyperbaric air in batch and fed-batch cultivation - Belo, Isabel (2000)
The effects of increased air pressure in a cul- ture of the thermophilic microorganism Thermus sp. RQ-1 were investigated. Cell growth dependence on oxygen supply was investigated in a fermenter at atmo- spheric pressure. Total oxygen depletion from the me- dium for low values of kLa was observed during the exponential growth phase. It was possible with this strain to enhance the oxygen transfer rate by increasing the air pressure. Cell productivity was improved by pressurisation up to 0.56 MPa for batch cultivation; and an induction of the antioxidant enzymes, superoxide dismutase and catalase, was observed with the rise in pressure. Cell pre-cultivation under pressurised condi- tions conferred to the cells more resistance to an exposure to hydrogen peroxide and more sensitivity to paraquat (methyl viologen). The usefulness of bioreactor pressurisation on the cultivation of Thermus sp. RQ-1 was demonstrated for fed-batch operation, with the at- tainment of higher cell densities. A two-fold increase in cell mass productivity was obtained by the use of hyperbaric air (0.5 MPa). With the pressurisation of the head-space in the reactor, it was also possible to elimi- nate the loss of liquid by evaporation, which amounted to more than 10% at 70 °C and atmospheric pressure.